2018
DOI: 10.1101/325290
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A systematic method for surveying data visualizations and a resulting genomic epidemiology visualization typology: GEViT

Abstract: Motivation: Data visualization is an important tool for exploring and communicating findings from genomic and healthcare datasets. Yet, without a systematic way of organizing and describing the design space of data visualizations, researchers may not be aware of the breadth of possible visualization design choices or how to distinguish between good and bad options. Results:We have developed a method that systematically surveys data visualizations using the analysis of both text and images. Our method supports … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
2
2
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(22 citation statements)
references
References 23 publications
1
21
0
Order By: Relevance
“…reminders for adding labels and legends, suggestions for optimal colour schemes, warnings in case of chart junk). Our results and findings from similar studies in other fields [23,24] can support them in doing so by providing an overview of what is already used, including potential pitfalls. Of note, academic journals play an important part in this process by providing the platform for data visualizations and should be encouraged to promote high quality data visualization practices.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…reminders for adding labels and legends, suggestions for optimal colour schemes, warnings in case of chart junk). Our results and findings from similar studies in other fields [23,24] can support them in doing so by providing an overview of what is already used, including potential pitfalls. Of note, academic journals play an important part in this process by providing the platform for data visualizations and should be encouraged to promote high quality data visualization practices.…”
Section: Discussionsupporting
confidence: 82%
“…The audience’s background and its familiarity with data visualization (the visual domain context) have to be taken into account in the design process to avoid these obstacles. Example studies that identified the visual domain context by studying the design space can be found in the field of genomic epidemiology and genomic data visualization [23,24]. Although, some recommendations and best practices exist that are helpful in the data visualization creation process, common data visualizations practices in the field of stewardship have yet to be revealed [25,26].…”
Section: Introductionmentioning
confidence: 99%
“…With pathogen genomic data, this is no longer true: these data need to be integrated to realize the full value of both. 31,86,87 Fortunately, academic research is addressing this challenge, 88 producing tools for visualizing and analyzing epidemiologic and phylogenetic data together, such as Microreact (microreact.org), 89 Nextstrain (nextstrain.org) 90 or the Interactive Tree of Life (itol.embl.de). 91 More broadly, the emerging field of data science offers novel approaches for integrating, analyzing and visualizing increasingly diverse public health data.…”
Section: Data Integration and Data Sciencementioning
confidence: 99%
“…A novel feature of our approach is that we tailor the recommendation for a specific domain, to tame the combinatorial explosion of possibilities that arise from a broad variety of input data types and output chart types. We leverage the knowledge encapsulated in a recent domainspecific visualization prevalence design space (VPDS), where visual design collections used by experts in a particular domain are both characterized and enumerated [6]. We use this domain-specific information in a few targeted stages of our recommender algorithm, in conjunction with many domain-agnostic decision procedures.…”
Section: Introductionmentioning
confidence: 99%
“…We use this domain-specific information in a few targeted stages of our recommender algorithm, in conjunction with many domain-agnostic decision procedures. The GEViT [6] VPDS that we proposed in previous work arises from genomic epidemiology (genEpi), a very appropriate exemplar domain for data recon with a diverse and heterogeneous set of input data types and output chart types; genEpi analysts often grapple with unfamiliar collections of datasets in situations where access is tightly controlled due to sensitive personally identifiable information.…”
Section: Introductionmentioning
confidence: 99%